Innovative Approaches to Increase Access to Medicines in Developing Countries - Stevens, Hilde; Huys, Isabelle (Frontiers in Medicine, 2017)
Access to essential medicines is problematic for one third of all persons worldwide. The price of many medicines (i.e. drugs, vaccines and diagnostics) is unaffordable to the majority of the population in need, especially in least-developed countries, but also increasingly in middle-income countries. Several innovative approaches, based on partnerships, IP and pricing, are used to stimulate innovation, promote healthcare delivery and reduce global health disparities. No single approach suffices, therefore stakeholders need to further engage in partnerships promoting knowledge and technology transfer in assuring essential medicines to be manufactured, authorized and distributed in low- and middle-income countries (LMICs) in an effort of making them available at affordable and acceptable conditions.